Perbedaan Kemampuan Bahasa Menurut Jenis Kelamin pada Siswa SLB Autis di Surakarta - Endang Susilowati Ningsih; Aris Sudiyanto; Nur Hafidha Hikmayani (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background:Knowledge about language in autism are lacking or else contradictive. Previous studies found that girls with autism spectrum disorder (ASD) had greater communication deficits than boys,while other studies mentioned that boys with ASD had less languagecapabilities than girls.This study aimed to examine the difference in language ability by genderamongstudents of autis schools in Surakarta. Methods:This was an observational analytic study using cross-sectional approach, conducted from April to May 2013 in SLB Autis Harmony and SLB Autis Alamanda Surakarta. Students of SLB Autis Harmony and SLB Autis Alamanda who met inclusion criteria were sampled. Subjects were categorized into verbal and nonverbal type. Data were analyzed using Fisher's exact test. Results:Of 33 subjects meeting the restriction criteria, 19 (57.6%) had language skills of nonverbal type, and 13 students (68.4%) of whom were boys. Statistical analysis showed no difference in language abilities of autistic boys and girls (p = 1.000). Conclusions:There was no language skill differenceaccording to gender of students with autism in SLB Autis Harmony and SLB Autis Alamanda Surakarta. Keywords:autism, language, gender.